19F Magic Angle Spinning Dynamic Nuclear Polarization Enhanced NMR Spectroscopy. Issue 22 (23rd April 2019) - Viger‐Gravel, Jasmine; Avalos, Claudia E.; Kubicki, Dominik J.; Gajan, David; Lelli, Moreno; Ouari, Olivier; Lesage, Anne; Emsley, Lyndon
Abstract: The introduction of high‐frequency, high‐power microwave sources, tailored biradicals, and low‐temperature magic angle spinning (MAS) probes has led to a rapid development of hyperpolarization strategies for solids and frozen solutions, leading to large gains in NMR sensitivity. Here, we introduce a protocol for efficient hyperpolarization of 19 F nuclei in MAS DNP enhanced NMR spectroscopy. We identified trifluoroethanol‐ d 3 as a versatile glassy matrix and show that 12 mm AMUPol (with microcrystalline KBr) provides direct 19 F DNP enhancements of over 100 at 9.4 T. We applied this protocol to obtain DNP‐enhanced 19 F and 19 F– 13 C cross‐polarization (CP) spectra for an active pharmaceutical ingredient and a fluorinated mesostructured hybrid material, using incipient wetness impregnation, with enhancements of approximately 25 and 10 in the bulk solid, respectively. This strategy is a general and straightforward method for obtaining enhanced 19 F MAS spectra from fluorinated materials. Abstract : Faster and faster : A 19 F MAS DNP enhanced NMR technique was developed by using an optimized polarizing solution of 12 mm AMUPol in trifluoroethanol‐ d 3 (with microcrystalline KBr), providing 19 F signal enhancements of a factor of 118. Application to an active pharmaceutical ingredient and fluorinated materials yielded 19 F and 19 F– 13 C CP spectra with a saving time of a factor of up to 600.